A Study Of Factors Influencing Consumer Purchase Decisions Through Celebrity Endorsement - Deepak Tyagi, Dr. Manoj Aggarwal (European Economic Letters (EEL), 2025)
The goal of the study is to investigate the elements that impact customers' purchasing decisions through celebrity endorsements. The questionnaire identified appropriate characteristics linked to celebrity endorsement, advertising, and customers' purchasing decisions were meticulously documented so that valid inferences could be derived. According to the research, gender and education have little effect on customer demographics. The result shows that there is no gender difference in customers' purchase decisions on celebrity endorsements in commercials. Male and female had similar perspectives.